A simple 3D elastoplastic constitutive model for soils based on the characteristic stress. (May 2019) - Lu, De-chun; Li, Xiao-qiang; Du, Xiu-li; Liang, Jing-yu
Abstract: This paper presents a direct method to establish a 3D elastoplastic constitutive model for soils based on the characteristic stress. In the established model, a new yield function is first formulated through an interpolation function in the characteristic stress space. A hardening parameter that suits for monotonic and cyclic loading conditions is established by introducing the concept of the subloading surface. Then, a 3D constitutive model for soils is established by combining the previously proposed plastic potential function. Only seven material parameters with clear physical meanings are included in the proposed 3D elastoplastic model. The deformation behaviours of soils under monotonic and cyclic loading conditions and the critical state properties under true triaxial stress conditions are analysed on the basis of the presented model. The capability of the model is verified by the comparisons between the model responses and the test results of soils under the 3D monotonic and cyclic loading conditions.